(Na, □)5[MnO2]13 nanorods: a new tunnel structure for electrode materials determined ab initio and refined through a combination of electron and synchrotron diffraction data. Issue 6 (2nd December 2016) - Mugnaioli, Enrico; Gemmi, Mauro; Merlini, Marco; Gregorkiewitz, Michele
Abstract : Octahedral molecular sieves (OMS) attract increasing interest in the search for novel electrode materials for energy storage and water desalination. While a nanometric particle size is desirable for such applications, this makes ordinary single‐crystal characterization difficult and many OMS structures are still waiting for elucidation. Here we present the long awaited structure of a well known material, (Na, □)5 [MnO2 ]13, resolved by a combination of electron diffraction tomography, dynamical scattering theory and X‐ray powder Rietveld refinement. A new type of tunnel structure was found, able to explain previously reported electrochemical properties. This structure also suggests a possible mechanism for topotactic transformations between different manganese oxide OMS frameworks. Abstract : (Na x □1 − x )5 [MnO2 ]13 has been synthesized with x = 0.80 (4), corresponding to Na0.31 [MnO2 ]. This well known material is usually cited as Na0.4 [MnO2 ] and is believed to have a romanèchite‐like framework. Here, its true structure is determined, ab initio, by single‐crystal electron diffraction tomography (EDT) and refined both by EDT data applying dynamical scattering theory and by the Rietveld method based on synchrotron powder diffraction data (χ 2 = 0.690, R wp = 0.051, R p = 0.037, R F 2 = 0.035). The unit cell is monoclinic C 2/ m, a = 22.5199 (6), b = 2.83987 (6), c = 14.8815 (4) Å, β = 105.0925 (16)°, V = 918.90 (4) Å 3, Z = 2. A hitherto unknown [MnO2 ] framework is found, which is mainly based on edge‐ and corner‐sharing octahedra and comprises three types of tunnels: per unit cell, two are defined by S‐shaped 10‐rings, four by egg‐shaped 8‐rings, and two by slightly oval 6‐rings of Mn polyhedra. Na occupies all tunnels. The so‐determined structure excellently explains previous reports on the electrochemistry of (Na, □)5 [MnO2 ]13 . The trivalent Mn 3+ ions concentrate at two of the seven Mn sites where larger Mn—O distances and Jahn–Teller distortion are observed. One of the Mn 3+ sites is five‐coordinated in a square pyramid which, on oxidation to Mn 4+, may easily undergo topotactic transformation to an octahedron suggesting a possible pathway for the transition among different tunnel structures.